Phytotoxic, antibacterial, and antioxidant activities of mycotoxins and other metabolites from Trichoderma sp. Issue 23 (2nd December 2017) - Zhang, Ju-cheng; Chen, Guang-Yi; Li, Xiao-Zhan; Hu, Ming; Wang, Bang-Yan; Ruan, Bao-Hui; Zhou, Hao; Zhao, Li-Xing; Zhou, Jun; Ding, Zhong-Tao; Yang, Ya-Bin
Abstract: A new natural mycotoxin was isolated from the fermentation broth of Trichoderma sp. Jing-8 and the structure was determined as alternariol 1′-hydroxy-9-methyl ether (1 ), together with twelve known compounds. The structures were elucidated on the basis of their 1D, 2D NMR spectra and mass spectrometric data. Compounds 1, 8 and 9 indicated inhibitions against germination of the seeds of cabbage with MICs < 3 μg/mL. The compound 1 showed the antibacterial activity against Bacillus subtilis and Staphylococcus aureus with MICs at 64 μg/mL. Compound 1 and 3 showed significant DPPH radical-scavenging activities with IC50 at 12 μg/mL, respectively. The OH at C-1′ in compound 1 decreased the cytotoxicity of these mycotoxins. A primary structure–activity relationship about the alternariol derivatives was discussed. Compounds 2 –7 and 8 were the first time to be isolated from the Trichoderma . Abstract :